A 10 ka intentionally deformed human skull from Northeast Asia. (18th April 2022) - Yin, Qiyu; Li, Qiang; Zhang, Hucai; Ma, Ning; Zhang, Wei; Ni, Xijun
Abstract: The oldest‐known undoubted cultural practices of intentional cranial deformation (ICD, also known as artificial cranial modification) appeared in the Middle East, Australia, and Northeast China in the terminal Pleistocene‐early Holocene populations. Here, we report an ICD calvarium fossil (Songhuajiang II) discovered from an underwater sand mining site near Harbin City in Northeast China. With a calibrated accelerator mass spectrometry (AMS) radiocarbon age of 11, 095–10, 745 BP, the fossil calvarium is among the oldest‐known ICD records in the world. A combination of pronounced superciliary arches, salient temporal lines, and relatively round and dull supraorbital margin, together with moderately wide interorbital space, flat glabella region without infraglabellar notch, flat and small zygomatic trigon, round and inclined superior‐lateral orbital margin, and largely closed sutures, suggests that Songhuajiang II skull belonged to a middle‐aged Asian man. The man has flat frontal and occipital bone, conical posterior parietal region, and a circular depression posterior to the coronal suture, and more subdivisions and many crenulated terminal branches on the anterior branch of the middle meningeal vessels. These features are typical for the tabular deformation methodology of ICD. The discovery, together with previously known ICD records (Songhuajiang I, Qianguo Man Qingshantou 1, and Djalai‐Nor cranium), suggests that the ICD cultural practice has a long and continuous history in Northeast Asia.